Al-Lugah al-ʼArabiyyah wa Tahaddiyyātuhā fī ʼAṣr al-ʼAwlamah - Basyiri Abd. Muthi Sayid Darwisy (Al-Zahra : Journal for Islamic and Arabic Studies, 2006)
Arabic language is one of official language in United Nations. Beside, Al-Qur’an as the main source of Islamic rules uses Arabic language. This paper describes the existence and the challenge of Arabic language in Global era.